Lipedematous Alopecia: Clinical, Histopathological, and Trichoscopic Findings of a Single Case and Review of the Literature - Ornella Accaputo; Jonathan Michael White; Athanassios Kolivras; Niloufar Sadeghi; Evelyne Berlingin; Véronique del Marmol (Karger Publishers, 2019)
A 66-year-old African woman suffered from a boggy thickening of the scalp in the frontoparietal area and the vertex accompanied by headache since infancy. In her thirties, she developed diffuse hair loss in the same area. Clinical and trichoscopic examination were unhelpful, but the histopathological and radiologic findings led to a diagnosis by demonstrating thick subcutaneous adipose tissue. First described in 1935 by Cornbleet [Arch Dermatol Syphilol. 1935; 32: 688], lipedematous scalp is a rare scalp disease marked by a soft thickening of the scalp. A similar clinicopathologic entity associated with nonscarring but permanent acquired alopecia was described in 1961 by Coskey et al. [Arch Dermatol. 1961 Oct; 84(4): 619-22] and termed lipedematous alopecia. In this article, we report a rare case of lipedematous alopecia with emphasis on a trichoscopic and histopathological description with review of the literature. Our case highlights the importance of palpation during the clinical examination. It remains to be determined whether this is actually a specific disease entity or a combination of 2 separate conditions. Symptomatic treatment is advisable given the lack of robust published data on treatment. Only 40 cases of lipedematous alopecia and 52 cases of lipedematous scalp have been published in the literature. Our case is the 93rd.